2005
DOI: 10.1175/mwr2923.1
|View full text |Cite
|
Sign up to set email alerts
|

New Approach to Calculation of Atmospheric Model Physics: Accurate and Fast Neural Network Emulation of Longwave Radiation in a Climate Model

Abstract: A new approach based on a synergetic combination of statistical/machine learning and deterministic modeling within atmospheric models is presented. The approach uses neural networks as a statistical or machine learning technique for an accurate and fast emulation or statistical approximation of model physics parameterizations. It is applied to development of an accurate and fast approximation of an atmospheric longwave radiation parameterization for the NCAR Community Atmospheric Model, which is the most time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
148
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 179 publications
(170 citation statements)
references
References 20 publications
2
148
0
1
Order By: Relevance
“…In particular, neural networks (NN) have exploded in popularity in recent years [Goodfellow et al, 2016]. In an early paper, Krasnopolsky et al [2005] showed that a NN can emulate a realistic radiative transfer code but with much lower computational expense. They, then, trained a NN-based cumulus parameterization using a limited-area CRM, and showed that the scheme could accurately diagnose cloud fractions and precipitation [Krasnopolsky et al, 2010[Krasnopolsky et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, neural networks (NN) have exploded in popularity in recent years [Goodfellow et al, 2016]. In an early paper, Krasnopolsky et al [2005] showed that a NN can emulate a realistic radiative transfer code but with much lower computational expense. They, then, trained a NN-based cumulus parameterization using a limited-area CRM, and showed that the scheme could accurately diagnose cloud fractions and precipitation [Krasnopolsky et al, 2010[Krasnopolsky et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the complexity of the physical processes involved and the complexity of their mathematical and numerical representations, some of these parameterizations are the most time-consuming components of GCMs. We have developed NN emulations for the most time-consuming part of model physics: model radiation [9][10][11][12][13]. Because, as it was mentioned above, a physically based parameterization is represented by a single mapping, we successfully used a single NN to emulate a physically based parameterization.…”
Section: Introductionmentioning
confidence: 99%
“…Chevallier et al (1998) and Krasnopolsky et al (2005) have developed neural network schemes that can emulate radiative transfer calculations with much greater efficiency than correlated-k methods. These may then be used at much higher sampling resolutions.…”
Section: Introductionmentioning
confidence: 99%